Reflections on The Challenges and Opportunities Prior to Digital Transformation: English Teacher Competence at SMPN 2 Mootilango - Bantulu, Yusna; Maharuju, Rostin; Basalamah, Nonny (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
This study evaluates the proficiency of english teachers at SMPN 2 Mootilango before digital transformation, with the objective of identifying issues in pedagogical methods, classroom management, and the utilization of instructional media. A qualitative case study approach was utilized to collect data via classroom observations, semi-structured interviews, and document analysis. The findings demonstrate that teacher-centered instruction, dependence on rote memorization, and inadequate classroom management practices substantially impeded student involvement and language acquisition. Moreover, inadequate instructional resources and insufficient professional development opportunities hindered pedagogical creativity. These findings highlight the imperative for adaptive professional development programs that furnish educators with varied techniques, irrespective of technological accessibility